2021
DOI: 10.21203/rs.3.rs-141063/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The long noncoding RNA AATBC promotes breast cancer migration and invasion by interacting with YBX1 and activating the YAP1/Hippo signaling pathway

Abstract: BackgroundLong noncoding RNAs (lncRNAs) play an important role in the regulation of gene expression and are involved in several pathological responses. However, many important lncRNAs in breast cancer have not been identified and their expression levels and functions in breast cancer remain unknown.MethodsWe used the microarray data to identify differentially expressed lncRNAs between breast cancer and adjacent breast epithelial tissues. In vitro and in vivo assays were used to explore the biological effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…For instance, upregulation of AATBC was observed in breast cancer, which accelerates the metastasis of breast cancer by negatively modulating YBX1 and activating the YAP1/ Hippo signaling pathway. 13 Similarly, a promoted effect of AATBC has been observed in the proliferation and migration of prostate cancer cells via the regulation of the miR-1245b-5p/CASK axis. 14 Based on previous findings that AATBC is a dysregulated lncRNA in cervical cancer, its potential functional role in cervical cancer was evaluated in the present study.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…For instance, upregulation of AATBC was observed in breast cancer, which accelerates the metastasis of breast cancer by negatively modulating YBX1 and activating the YAP1/ Hippo signaling pathway. 13 Similarly, a promoted effect of AATBC has been observed in the proliferation and migration of prostate cancer cells via the regulation of the miR-1245b-5p/CASK axis. 14 Based on previous findings that AATBC is a dysregulated lncRNA in cervical cancer, its potential functional role in cervical cancer was evaluated in the present study.…”
Section: Discussionmentioning
confidence: 93%
“…In a recent study, Li et al screened 130 dysregulated lncRNAs in cervical cancer using the lncRNA microarray analysis, wherein the alerting expression of lncRNA AATBC (AATBC) was observed 11 . AATBC was suggested to regulate the progression of various human cancers, such as nasopharyngeal carcinoma, prostate cancer, breast cancer, and bladder cancer; AATBC was also found to be dysregulated in each of these conditions 12–15 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…LncRNAs are important in gene regulation. 33 LncRNA interacts with many transcription factors and affects lung cancer growth and spread. 13,34 To date, many lncRNAs have been shown to be associated with the diagnosis and prognosis of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular level QPCR results showed that six TMErelated prognostic genes were dysregulated in expression between BCa cells and normal bladder epithelium, suggesting that dysregulated expression levels of these genes play an important role in the development of BCa. Zhang et al (44) reported that GATA3-AS1 promoted the development and metastasis of triple-negative breast cancer by stabilizing tumor immune escape, while Wang et al (45) found AATBC was closely associated with breast cancer metastasis. Further, Sun et al (46) found that TGR-AS1 promoted hepatocellular carcinoma invasion and metastasis by regulating the EMT pathway, and Zhang et al (47) found that LINC01833 promoted EMT function.…”
Section: D Ementioning
confidence: 99%